Analisis Penerapan Sistem Informasi Manajemen Email IMS Di PT. IBU - Ageng Saepudin Kanda; Ratna Intan Sari (Pusat Riset dan Inovasi Nasional, 2024)
The IMS application program is an application for sending files or data that is used in the form of email to help send files between departments. The use of this application program is aimed at all business people in the company, from directors to admins. The aim of this research is to determine the extent to which the IMS management information system is implemented in business operational activities and whether the system is functioning optimally or not. This research uses descriptive qualitative research methods, such as reading reference books, journals and articles written by experts to obtain accurate data and prevent data manipulation. The subject of this research is an email application, namely. IMS. The results of this research show that the management information system has been implemented optimally, starting with training at the start of use, to ensure user comfort and satisfaction. In addition, the IMS application management information system has a very good impact on the business as a whole.